Zonation system in admission of new student at state secondary school in Indonesia: how predictable to learning success - B. Bulkani; M. Fatchurahman; M. A. Setiawan (Образование и наука)
Introduction. A new student acceptance model with the zoning system raises various problems, including the unequal number of public schools in an area causing students to experience barriers to obtaining a proper education. The decrease in motivation and achievement of students is because the selection is only based on zoning, and the achievements of prospective students at the previous education level are not considered. Students fail to enter superior schools because they are outside the zone. The distribution of quality public schools are not evenly distributed, causing limited choices and causing the implementation of the principle of justice in access to education services – lack of readiness of local governments in setting zones.Aim. From the problems above, this study aims to find differences in learning achievement in terms of admission, predict learning achievement from elementary school to junior high school, and determine graduation document predictions with a zoning system on student achievement.Research methodology and methods. The research used a quantitative approach from October 2021 to March 2022. The research sample was 356 students who entered the 2018 state junior high school and graduated from the 2020 school year junior high school. The sampling technique for this study used proportional random sampling. Determining the size of the research sample was done by considering the pathways for accepting new students: the zoning path, the achievement path, the affirmation path, and the parent transfer path. Data analysis used ANOVA and multiple regression analysis at a significance level of 5%.Results and scientific novelty. The results showed no difference in the average report cards of junior high school students when viewed from the path when they entered the junior high school through the zoning system. The results of one-way ANOVA obtained F = 1.298 with a significance level of 0.275. The differences in the entry paths of students to junior high school, namely from the zoning pathway, academic and non-academic achievement pathways, affirmation pathways, and parental transfer paths, are proven not to affect their learning achievement in junior high schools. There is a linear regression from students’ learning achievement in elementary school to students’ learning achievement in junior high school. The partial and simultaneous tests show that it is not proven that learning achievement in elementary school affects learning achievement in junior high school. When they graduate from elementary school, students’ learning achievement has a weak predictive power on students’ learning achievement in junior high school. The national primary school-based school examination average, elementary school report card average, and elementary school examination average, used as entry requirements to junior high school in the zoning system, only have a predictive power of 1.4–2,7%.Practical significance. Parents can use this research to make decisions on their child’s education. Parents do not need to worry about the zoning system implemented by the government in accepting new students because the zoning system does not affect children’s achievements at the level of education they take. The school must also implement education systems and policies properly so that the quality of education in each institution is maintained so that parents do not worry about choosing a place for their child’s education.